Professor Tadeusz Powałowski - of Archives of Acoustics, Editorial Board (Archives of Acoustics, 2008)
On January 11, 2008 Professor Tadeusz Powałowski passed away forever.The Polish science and all of us have suffered a great loss of a scientist who was an authority on ultrasonic diagnostic methods of the human vascular system.Professor Tadeusz Powałowski was born on October 30, 1945 in Wągrowiec, Poland. He received his M.Sc. degree in Electronics from Warsaw University of Technology in 1969. He obtained his Ph.D. degree and earned his D.Sc. degree from the Polish Academy of Sciences in 1976 and 1986, respectively. He obtained full Professor degree in 2001. Professor Powałowski has spent an extended period of time as Visiting Scientist at Queen's University in Kingston, Canada. Professor Powałowski has made important contributions to the field of biomedical ultrasound; in particular, his research contributed to the advances in ultrasonic methods and instrumentation for the diagnosis of the human vascular system. In 1996 he obtain the Award of the Techno-Messe Kensai in Osaka (Japan) and avard the Ministry of Science (Development of Ultrasonic Apparatus "Vascular Echo Doppler" (VED) for noninvasive ultrasonic examinations of the blood flow and the elasticity of arterial wall. Author of numerous scientific papers and patents in this field. Among different important positions held in the field of Polish Acoustics Professor Tadeusz Powałowski was:V-ce President of the Acoustical Committee of the Polish Academy of Sciences,President of the Warsaw Chapter of the Polish Acoustical Society,Editor-in-Chief of the "Archives of Acoustics".We shall always remember Professor Tadeusz Powałowskii not only as a scientist, but also as a modest man who was, always ready to help others and sensitive to their needs.